Supply shocks in the market for apprenticeship training - Mühlemann, Samuel [Verfasser]; Dietrich, Hans [Verfasser]; Pfann, Gerard A. [Verfasser]; Pfeifer, Harald [Verfasser] (My University, 2022)
„In times of economic crisis and increasing costs of obtaining academic qualifications, a dual vocational system that combines firm-level training with vocational schooling is gaining popularity in many countries. For example, the United Kingdom and the United States recently launched programs to foster dual apprenticeship training tracks for young school leavers. In addition, owing to the economic downturn following the COVID-19 pandemic, increasing youth unemployment rates are likely to raise policymaker interest in apprenticeship programs that smooth the transition from education to the labor market. Governments expect substantial returns with such investments, most importantly through improving young job seekers’ employability, skills, and future careers. […] Our study aims to shed light on the effect of a positive supply shock on the equilibrium price and quantity in the market for apprenticeship training. To predict the possible outcomes, we first present a simple theoretical model of the market for two types of school graduates (lower secondary school and high school graduates). In competitive training markets and under the assumption that apprentices with different levels of education are substitutes, we expect that a one-time supply shock of high school graduates leads to an increase (decrease) in the number of apprenticeship contracts among apprentices with a high school (lower secondary school) degree and a decrease (increase) in the wage for high school (lower secondary school) graduates. However, the assumption of competitive markets may be particularly strong in the context of the German apprenticeship market, as apprentice wages are subject to collective bargaining agreements across a wide range of training occupations, and employer associations and unions are involved in many aspects of apprenticeship training, both formally and informally. To the extent that institutions in Germany lead to frictions in the apprenticeship market, theory predicts that a supply shock of highly educated apprentices would be absorbed by training firms if wages were below the competitive level prior to the supply shock. As a result, a positive supply shock would lead to more apprenticeship contracts without negatively affecting wages.” (excerpt; BIBB-Doku)
Keywords: G 1.3.1.1 Ausbildungsstellenmarkt; G 1.2.2.1 Lohn- & Tarifsysteme; S 3.2 Unternehmen und Behörden; 370; 330; Schulabgänger; Schulabschluss; Bildungsentscheidung; Ausbildungsstellenmarkt; Ausbildungsplatzangebot; Ausbildungsplatznachfrage; Substitution; Ausbildungsverhalten; Lohnhöhe; Lohnentwicklung; Bundesländer